The future of audit (Journal of Information Systems and Technology Management, 2014)
The purpose of this study is to discuss the current state and future of auditing. Expert consensus is used as a basis to examine the current state of auditing and generate modifications both needed and likely to occur in the audit profession. This study contributes to the literature by using the Delphi method to develop predictions as to the direction of the audit industry and discuss the implications associated with these predictions. If auditors can better understand where the profession stands and where it is headed, then they can better prepare for the future. Some predictions emerging from this study relative to future audit practices include increasing automation of audit procedures, more predictive financial statements, continuous auditing of financial statements and transactions, and an increasingly global perspective regarding audit activities.